2018
DOI: 10.1038/s41580-018-0060-8
|View full text |Cite
|
Sign up to set email alerts
|

A new era for understanding amyloid structures and disease

Abstract: The aggregation of proteins into amyloid fibrils and their deposition into plaques and intracellular inclusions is the hallmark of amyloid disease. The accumulation and deposition of amyloid fibrils, collectively known as amyloidosis, is associated with many pathological conditions such as A disease P , type II diabetes, and dialysis related amyloidosis.However, elucidation of the atomic structure of amyloid fibrils formed from their intact protein precursors and how fibril formation relates to disease has rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
695
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 766 publications
(746 citation statements)
references
References 291 publications
11
695
0
6
Order By: Relevance
“…Amyloid aggregates are signatures of various neurodegenerative disorders such as Alzheimer’s and Parkinson’s diseases, and small soluble oligomeric intermediates formed during amyloid fibrillation are typically associated with cytotoxicity [24, 25]. Although many amyloid aggregates share a common cross- β sheet structural motif that is an assembly of identical copies of amyloid peptides, oligomers and fibrils are highly heterogeneous in terms of their structure and size [26, 27]. Interestingly, not all aggregation intermediates are equally toxic [28].…”
Section: Resolving Structural Heterogeneities Within Amyloid Fibersmentioning
confidence: 99%
“…Amyloid aggregates are signatures of various neurodegenerative disorders such as Alzheimer’s and Parkinson’s diseases, and small soluble oligomeric intermediates formed during amyloid fibrillation are typically associated with cytotoxicity [24, 25]. Although many amyloid aggregates share a common cross- β sheet structural motif that is an assembly of identical copies of amyloid peptides, oligomers and fibrils are highly heterogeneous in terms of their structure and size [26, 27]. Interestingly, not all aggregation intermediates are equally toxic [28].…”
Section: Resolving Structural Heterogeneities Within Amyloid Fibersmentioning
confidence: 99%
“…44 However, the predicted structure of BBF2H7 does not contain β-sheet structures. 49 In this study, we found that BSP fragments also exhibit high aggregation propensity and form fibrils. 45 The β-sheet form of α-synuclein shows higher aggregation propensity than those of random-coil form.…”
Section: Discussionmentioning
confidence: 64%
“…There is controversy about which forms of proteins are toxic in neurodegenerative disorders. While some studies attribute toxicity to the aggregated form, other studies suggest aggregation to be a beneficial process that protects the cell from intermediate or misfolded toxic proteins [138,139]. Neurodegenerative diseases such as Alzheimer's disease (AD) and Parkinson's disease (PD) are also discussed as potential prion-like diseases for which misfolded proteins are known to propagate and convert other proteins into pathological forms [140,141].…”
Section: Targeted Proteolysis Via Lysosomes or The Ermentioning
confidence: 99%